Free trade with Korea: Economic and political opportunities for Europe - Hanns Günther Hilpert (Stiftung Wissenschaft und Politik (SWP), 2009)
For the first time ever, the EU is concluding a free trade agreement with an Asian country. After 26 months of arduous negotiations, the Republic of Korea and the EU have agreed on the comprehensive liberalization of their trade and economic relations. The free trade zone between Europe and South Korea will in fact be the second-largest worldwide. Situated at opposite ends of the Eurasian land mass, Europe and the Korean peninsula will come closer through the agreement - both politically and economically. However, there is remarkable resistance to the Korea-EU Free Trade Agreement (KOREU FTA) in some sectors of the European economy, suggesting that ratification is by no means guaranteed. Europe's automotive industry, for example, considers KOREU to be unbalanced. Yet from a broader economic perspective, the agreement should be seen in a positive light. It bears great potential - especially for the German export industry, which has been badly scarred by the financial crisis. From a trade policy perspective, KOREU will send out a positive signal countering the worldwide trend toward protectionism
Keywords: 320